A clinical example of the treatment of a patient using a hybrid device for rapid palatal expansion - A. A. Bazan; N. S. Drobysheva (Эндодонтия Today)
While using a clinical case as an example, in this article we described the usage of an expanding appliance based on palatal orthodontic mini-implants for the upper jaw.